Strategi Perekrutan Santri Pondok Pesantren Salafiyah Ibnu Qasim Desa Tassiwalie Kecamatan Suppa Kabupaten Pinrang - Nur Dewi Muh. Nur; Abd. Halim K; Muhiddin Bakri (Institut Agama Islam Negeri Parepare, 2021)
This study aims to determine the strategy of recruiting students carried out by the Salafiyah Ibnu Qasim Islamic boarding school, Tassiwalie Village, Suppa District, Pinrang Regency and the obstacles it faces. This study uses a descriptive qualitative approach. Data collection techniques used are field research, such as observation, interviews and documentation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results of this study indicate that the recruitment strategy carried out by the Salafiyah Ibnu Qasim Islamic boarding school is in the form of carrying out several approach activities that can establish good relations with the community, such as attending or attending events held by the community, and also inviting the community to attend the events held, sending students in each area to conduct sermons and lectures, and also provide free registration fees. The obstacle in recruiting students is inadequate learning facilities. There are several indicators of the success of recruiting students at the Salafiyah Ibnu Qasim Islamic boarding school, including this Islamic boarding school that has quality in terms of good attitudes and morals as well as mastering qualified knowledge in the field of religion